Analisis Spasial Kejadian Demam Berdarah di Kota Padang Tahun 2018-2022 - Fadillah Ulva; Nailul Hikmi (JIK-JURNAL ILMU KESEHATAN, 2024)
In 2020, the number of dengue fever cases in Indonesia that was reported was 95,893 cases with 493 deaths. The incidence rate of dengue fever in Indonesia in 2020 was 49 per 100,000 population with a CFR of 0.51%. The incidence rate of dengue fever cases in Indonesia in 2021 is 27.5 cases per 100,000 population and the CFR is 0.97%. DHF cases in Indonesia continue to experience a significant increase. In 2022, the number of dengue fever cases in Indonesia will be 143,184 cases, with the number of deaths due to dengue fever reaching 1,236 cases. Until now, dengue fever is still a public health problem in Indonesia, including in West Sumatra. This is proven by the discovery of dengue fever cases in almost all districts/cities in West Sumatra. The West Sumatra Provincial Health Service recorded 4,024 cases of dengue fever occurring during 2022. The district/city with the highest dengue fever cases was the city of Padang with 824 cases, followed by Pesisir Selatan with 479 cases, and Tanah Datar with 458 cases. The aim of this research is to determine the spatial description of the incidence of dengue fever based on climate and population density in Padang City in 2018-2022. This research uses an analytical descriptive observational ecological study method. This research was carried out in Padang City in 2023 using data from 2018-2022. The data used is secondary data obtained from the West Sumatra Provincial Health Service and the West Sumatra Central Statistics Agency. Based on spatial analysis, it is known that the highest cases in Padang City are in Kuranji District. Based on the results of statistical analysis, it is known that there is a significant relationship between average rainfall and rainy days and the incidence of dengue fever in Padang City and there is no significant relationship between average air temperature and the incidence of dengue fever in Padang City.